The Impact of Structure, Environment, and Interdependence on the Perceived Usefulness of Management Accounting Systems - Chenhall, Robert H.; Morris, Deigan (The Accounting Review, 1986)
[This paper examines the effect of structural decentralization, perceived environmental uncertainty, and organizational interdependence on Management Accounting Systems [MAS] design. MAS design was defined in terms of the perceived usefulness of several information characteristics which may be associated with an MAS. These characteristics were scope, timeliness, level of aggregation, and information which assists integration. In addition to examining the direct effects of contextual variables, the study sought to determine how the independent variables interacted. Hypotheses were generated for both direct and indirect effects of contextual variables and were tested using data collected from 68 managers. The findings indicated that: 1) Decentralization was associated with a preference for aggregated and integrated information; perceived environmental uncertainty with broad scope and timely information; organizational interdependence with broad scope, aggregated, and integrated information. 2) The effects of perceived environmental uncertainty and organizational interdependence were, in part, indirect through their association with decentralization.]